2019
DOI: 10.1159/000496839
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Restless Legs Syndrome in Korean Adults: A Study in Two Independent Samples of the General Population

Abstract: Background: Restless legs syndrome (RLS) is a common sleep disorder, although it has a low prevalence in Asian populations. However, the reported RLS prevalence in ­Korean adults is mostly 4.5–12.1%, which is higher than that reported in other Asian populations. This study aimed to diagnose RLS and exclude mimicking conditions in 2 independent samples of Korean adults, and to compare its prevalence to that from previous studies performed in Asian countries. Methods: Study populations included a (1) nationwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
1
11
3
Order By: Relevance
“…In previous studies, young age [ 6 ], increasing age [ 5 , 12 , 15 , 16 ], male gender [ 13 , 16 ], female gender [ 5 , 15 ], low educational status [ 3 , 5 , 15 ], poor SES [ 3 ], history of consanguinity [ 13 ], history of smoking [ 5 , 13 ], history of alcohol usage [ 3 ], higher BMI [ 15 ], presence of depression [ 6 , 12 ], anxiety [ 6 ], stress [ 5 , 6 ], gastritis [ 15 ], anaemia [ 15 ], hypertension [ 15 ], diabetes mellitus [ 13 ], bronchial asthma [ 13 ] and habitual snoring practice [ 13 ] were associated with the presence of RLS among the participants.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, young age [ 6 ], increasing age [ 5 , 12 , 15 , 16 ], male gender [ 13 , 16 ], female gender [ 5 , 15 ], low educational status [ 3 , 5 , 15 ], poor SES [ 3 ], history of consanguinity [ 13 ], history of smoking [ 5 , 13 ], history of alcohol usage [ 3 ], higher BMI [ 15 ], presence of depression [ 6 , 12 ], anxiety [ 6 ], stress [ 5 , 6 ], gastritis [ 15 ], anaemia [ 15 ], hypertension [ 15 ], diabetes mellitus [ 13 ], bronchial asthma [ 13 ] and habitual snoring practice [ 13 ] were associated with the presence of RLS among the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The major strength of this study is the prospective design and the blinded linguistic analysis. Another strength is the inclusion of a large sample of consecutive RLS patients, with a sex ratio similar to the one reported for RLS prevalence in epidemiological data (Berger et al, 2004 ; Didriksen et al, 2017 ; Hening et al, 2004 ; Högl et al, 2005 ; Kim et al, 2019 ). A possible limitation is that all patients were interviewed by a female investigator: interviewer’s gender has been reported to cause a bias in responses about sensitive experiences or behaviours (which are reported more frequently to women by women (Harling et al, 2019 ) and to female voices by men (Dykema et al, 2012 )), or substance abuse (which seems to be reported more often to men by both women and men; Heeb & Gmel, 2001 ; Houle et al, 2019 )).…”
Section: Discussionmentioning
confidence: 99%
“…Movement leads to partial or complete relief, at least as long as the activity continues (Allen et al, 2018). Gender aspects are likely to play a role in RLS, as prevalence of the disease is about twice as high in women as in men (Berger et al, 2004;Didriksen et al, 2017;Hening et al, 2004;Högl et al, 2005;Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the former four minimal (6) or later revised four essential diagnostic criteria are used (7), RLS is reported in 7.2-10.6% of the Caucasian population (8)(9)(10)(11)(12)(13)(14). When so-called RLS mimics are excluded, significantly lower prevalence rates of 0.4-2.4% are seen in different samples (15,16). The proportion of patients in need of treatment is estimated to vary between 1.5 and 2.7% (15).…”
Section: Introductionmentioning
confidence: 99%